Phosphorus concentration, accumulation, and allocation in stem elongation and anthesis growth stages in some crop and weed species of Gramineae - arezoo abidi; ebrahim zeinali; afshin soltani; abdolreza gharanjiki (فیزیولوژی محیطی گیاهی, 2017)
Information on variations in concentration, accumulation, and allocation of phosphorus (P) in different species is important for improving the absorption and use efficiency of mineral nutrients, especially in poor soils. Hence, this experiment was conducted in order to study the variations in P concentration, accumulation, and allocation to various parts of plants in a number of gramineae crops and weeds in stem elongation and anthesis growth stages. The experiment was carried out in a completely randomized design with a factorial arrangement with three replications in an open field condition in Gorgan University of Agricultural Sciences using a low (4.85 mg kg-1) available P soil during 2015-2016 growing season. Treatments in the pot experiment included 7 crop and weed species of poaceae family including bread wheat, durum wheat, common barley, naked barley, triticale, wild oat, and canary grass and application and non-application of recommended N, P, and K chemical fertilizers. Based on the results, with fertilizer application, the concentration and accumulation of P significantly increased in all parts of plants except for root in both stages of stem elongation and anthesis. Under non-fertilization conditions, the average P concentrations of the aerial part of the plant at stem elongation and pollination stages were 3.9 and 1.9, respectively, which increased to 4.5 and 2.1 g kg-1 as a result of fertilization. Also, as a result of fertilization, the average P concentration accumulated in the aerial part of the plants increased from 0.92 to 3.2 mg plant-1 at the stem elongation and from 2.45 to 2.9 mg plant-1 at anthesis stage. During anthesis, the effect of plant species on P concentration in all parts of the plants was significant while during stem elongation, this effect was significant only for P concentration of stem and aerial parts of the plants under study. However, at both stages, accumulation of P in all parts and in the whole plant was significantly affected by plant species and the interaction effects of the species and fertilization. The average concentration of P in the aerial parts of the species varied from 2.9 to 4.7 g kg-1 at stem elongation and from 1.4 to 2.7 g kg-1 at anthesis stage. The results of the mean comparisons of the interaction effects showed no significant difference of P accumulation in different parts of the plant at stem elongation stage under unfertilized conditions, and that at anthesis stage, differences of P accumulation under non-fertilization conditions between species were much less than those of fertilization conditions.